Determinant for Organizational Commitment in Higher Education Institution in Malaysia: A Case Study in Universiti Kuala Lumpur - Sharina, Osman (2010)
This study examined the relationship between job characteristic and organizational culture towards the organizational commitment among the employees in Universiti Kuala Lumpur (UniKL). Data was gathered through distributed questionnaires answered by 115 respondents from employees in City Campus which located in Kuala Lumpur. Data was analyzed using the Statistical Package for Social Sciences (SPSS v.12) where descriptive analysis was used to analyze the social demographic variable of the respondent; Pearson Correlation was used to study the existence of the relationship and the Multiple Regression Analysis was used to analyze the level of significant relationship between job characteristics and organizational culture with the employees' organizational commitment. Findings of the study revealed that there is significant and positive relationship between organizational cultures with the organizational commitment in UniKL. However, no relationship is significant to the other determinant (job characteristics). The study has also indicated that the organizational culture is more dominant as a factor in influencing the organizational commitment.